Consumer perception and intention to subscribe to prepared meal plan services: Study on the Filipino market - Avila, Marella Dominique T. (Animo Repository, 2022)
In comparison to large corporations in the United States and the United Kingdom, subscription-based meal delivery service providers in the Philippines were small to medium enterprises. The majority of the subscription-based meal delivery services in the Philippines were ready-to-eat prepared meal plans with an emphasis on diets such as low-calorie, plant-based, and/or ketogenic diets. With this in mind, the researchers wanted to find out the extent of the behavioral determinants and intention of Metro Manila consumers towards subscription-based prepared meal plan services. In addition, the research would consider convenience as another behavioral determinant towards the prepared meal plan. This study was a quantitative study analysis. The data for this study would be collected using purposive sampling through surveys. Due to the COVID-19 pandemic's restrictions and ongoing lockdown, the research was only conducted through online channels. This would be done online for the sake of convenience, safety, and mobility constraints in light of the ongoing pandemic. Surveys was distributed on social media platforms for subscribers and non-subscribers. The study was confined to Metro Manila since most subscription-based meal plan providers deliver in the area. Descriptive and regression research design would be considered suitable for the study. The researchers obtained a total of 209 respondents for the study from residents in the National Capital Region. The data was examined using a software, Jamovi. This survey results suggested that since the Philippines is an Asian developing country, in comparison with the literature from western and developed countries, only few Filipinos patronize subscription-based meal plans. The demographic results suggested that the great majority of the respondents were either working population or young adults who are still in school. Despite the limited number of subscribers among the respondents, these findings refuted the researchers' supposition that high-earning time-poor professionals would most likely pay for a subscription, as the vast majority of respondents had never subscribed to a prepared meal delivery plan. A typical survey responder of the questionnaire was a young adult in the employment or actively enrolled in school, who’s from the middle to upper class and has never subscribed to a prepared meal delivery plan. According to the hypothesis analysis, all components of the Theory of Planned Behavior showed a substantial positive association with the Intention to Subscribe to a subscription-based prepared meal plan service. The only significant variables of Intention to Subscribe to a subscription-based prepared meal plan service were 'Attitude' and 'Subjective Norm.' The study was unable to support all of the hypotheses because the majority of the sample had not subscribed to a prepared meal plan service. With that, it raised the question of why perceived behavioral control and convenience, both of which have been shown to be important in prior research, were not as important for Filipino customers. With the results from the study, meal plan delivery services should focus on Attitude and Subjective Norms as a way to encourage potential customers to sign up for their services, as well as current customers to keep using them. Given that there are only a few researches on this topic, both qualitative and quantitative studies on their perspective would be quite valuable. More exploration into the correlations between the variables identified in this study was recommended. A various perspective on both the business operations and consumer insights would help this industry thrive in the future.